Socio-gerontechnology Interdisciplinary Critical Studies of Ageing and Technology (Taylor & Francis, 2021)
Social change in the 21st century is shaped by both demographic changes associated with ageing societies and significant technological change and development. Outlining the basic principles of a new academic field, Socio-gerontechnology, this book explores common conceptual, theoretical and methodological ideas that become visible in the critical scholarship on ageing and technology at the intersection of Age Studies and Science and Technology Studies (STS). Comprised of 15 original chapters, three commentaries and an afterword, the book explores how ageing and technology are already interconnected and constantly being intertwined in Western societies. Topics addressed cover a broad variety of socio-material domains including care robots, the use of social media, ageing in place technologies, the performativity of user involvement and public consultations, dementia care and many others. Together, they provide a unique understanding of ageing and technology from a social sciences and humanities perspective and contribute to the development of new ontologies, methodologies and theories that might serve as both critique of, and inspiration for, policy and design. International in scope, including contributions from the UK, Canada, USA, Germany, Norway, Denmark, Austria, The Netherlands, Spain and Sweden, Socio-gerontechnology is an agenda-setting text that will provide an introduction for students and early career researchers as well as more established scholars that are interested in ageing and technology.
English
Keywords: Child & developmental psychology; Disability: social aspects; Society & culture: general; Sociology; socio-gerontechnology; Alexander Peine; Barbara Marshall; Wendy Martin; Louis Neven; ageing; technology; gerontology; digital technology; age studies; science and technology studies; STS; social media; neighbourhoods; ageing-in-place; co-housing; activism; dementia; public policy; later life; new materialism; technoscience; agency; participatory methods; ageism